2020
DOI: 10.1371/journal.pone.0233861
|View full text |Cite
|
Sign up to set email alerts
|

Trends and patterns of second-hand smoke exposure amongst the non-smokers in India-A secondary data analysis from the Global Adult Tobacco Survey (GATS) I & II

Abstract: Objectives The primary objective of the present study was to compare the prevalence and patterns of secondhand smoke (SHS) exposure in the home, workplace, public places, and at all three places amongst the non-smoker respondents between the two rounds of Global Adult Tobacco Survey (GATS) in India. The secondary objectives were to assess the differences in various factors associated with SHS exposure among non-smokers. Study design This secondary data analysis incorporated data generated from the previous two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
(30 reference statements)
4
20
1
Order By: Relevance
“…In the research done by Yaragani et al [15], 82% of current tobacco consumers were found although, 49% reported smoking tobacco, they had tobacco chewing habits. These estimates are in line with details from the Global Adult Tobacco Survey 2016-17 [16,17]. The comparatively lower cost of these items and the less revealing nature of their use compared to smoking are the reasons for increasing the use of smokeless types of tobacco [18].…”
Section: Resultssupporting
confidence: 73%
“…In the research done by Yaragani et al [15], 82% of current tobacco consumers were found although, 49% reported smoking tobacco, they had tobacco chewing habits. These estimates are in line with details from the Global Adult Tobacco Survey 2016-17 [16,17]. The comparatively lower cost of these items and the less revealing nature of their use compared to smoking are the reasons for increasing the use of smokeless types of tobacco [18].…”
Section: Resultssupporting
confidence: 73%
“…18 19 In India, existing literature suggests that gender, age, ethnicity, education, income and smoking status are associated with awareness of the harmful effects of smoking. [20][21][22] As awareness contributes to a more considerable extent to behaviour modification and tobacco cessation practices, it needs to be studied in entirety concerning socioeconomic and regional distributions to get a clear view on this aspect. Within this context, we examined the awareness regarding the harmful effects of tobacco among the users (both smoked and smokeless) and non-users based on the secondary data analysis of GATS 2016-2017 and compared it with GATS 2009-2010.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The proportion of people protected by smoke-free legislations worldwide has increased from 3.0% in 2007 to 21.1% in 2018 ( Table 2). The largest countries in the world report significant decreases in the proportion of people exposed to secondhand smoke [13][14][15][16]. Existing evidence shows that countries that enact national legislative smoking bans reduce the population exposure to passive smoke and benefit from improved health outcomes, specifically of cardiovascular diseases [17].…”
Section: Reducing the Prevalence Of Smoking And Exposure To Secondhanmentioning
confidence: 99%